2013
DOI: 10.1098/rsta.2011.0562
|View full text |Cite
|
Sign up to set email alerts
|

Resource convergence and resource power: towards new concepts for material efficiency

Abstract: Material efficiency is not a panacea, but it lies at the intersection of many problems of global sustainability. Reducing the usage of a single material in a value chain may require ingenuity and wide cooperation, but conceptually it is not a problem. When the problem stretches to several resources in changing circumstances, we have to understand the linkages between resources and the power, and the influence of each resource in decision-making in different settings. In this paper, we concisely go from the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Computational tools have been applied in environmental fields (e.g. Kostoff et al 2008, Neff and Corley 2009, Altaweel and Bone 2012, Zamagni et al 2012, Vasara et al 2013, Cody et al 2015, Convertino et al 2016 using methods like bibliometrics and media analysis to describe the state of a field and to recommend interpretations and research directions. A growing number of bibliometric analyses, which assess patterns in bibliographic data, demonstrates interest by environmental researchers in use of such tools (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational tools have been applied in environmental fields (e.g. Kostoff et al 2008, Neff and Corley 2009, Altaweel and Bone 2012, Zamagni et al 2012, Vasara et al 2013, Cody et al 2015, Convertino et al 2016 using methods like bibliometrics and media analysis to describe the state of a field and to recommend interpretations and research directions. A growing number of bibliometric analyses, which assess patterns in bibliographic data, demonstrates interest by environmental researchers in use of such tools (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of bibliometric analyses, which assess patterns in bibliographic data, demonstrates interest by environmental researchers in use of such tools (e.g. Kugo et al 2005, Janssen 2007, Neff and Corley 2009, Altaweel and Bone 2012, Zamagni et al 2012, Vasara et al 2013, Wang et al 2014, Chen et al 2016. Authors in other fields have suggested the use of computational methods to aid literature reviews (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Vasara et al [21] discuss a more general phenomenon than the coupling of 'critical' to 'energy' concerns detected by Ayres and Talens Peiró. The development of biofuels as an alternative to fuel oils clearly depends on the (large-scale) availability of fertile land and fresh water for irrigation.…”
Section: Motivations For Materials Efficiencymentioning
confidence: 99%
“…Similarly, the conversion of coal to liquid fuel requires water, and most means to overcome water shortages demand increased energy input. Vasara et al [21], therefore, describe what they term 'resource convergence'-recognizing that many resource stresses and responses to those stresses are coupled to stresses and responses for other key resources (including energy, water, land, metals, chemicals and biomass). Material efficiency is, therefore, likely to become a priority strategy in the wider area of responding to resource stresses other than energy and emissions.…”
Section: Motivations For Materials Efficiencymentioning
confidence: 99%
See 1 more Smart Citation